2019
DOI: 10.1186/s13054-019-2468-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in characteristics and outcomes of acute kidney injury on renal replacement therapy in intensive care units: analysis of a nationwide administrative database in Japan, 2007–2016

Abstract: Background We aimed to examine recent trends in patient characteristics and mortality in patients with acute kidney injury (AKI) receiving renal replacement therapy (RRT), including continuous RRT (CRRT) and intermittent RRT (IRRT), in intensive care units (ICUs). Methods From the Diagnosis Procedure Combination database in Japan during 6 months (July–December) from 2007 to 2016, we identified patients with AKI who received RRT in ICUs. We restricted the study participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Medina-Liabres KRP and Kim S. CRRT in the elderly to 68.7 years over a 10-year period (p for trend < 0.01) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Medina-Liabres KRP and Kim S. CRRT in the elderly to 68.7 years over a 10-year period (p for trend < 0.01) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In case of critically ill patients, the overall in-hospital mortality in patients with AKI on dialysis consistently decreased, and the mortality of those with AKI on dialysis was relatively lower than that of the RRT group with OHCA; this is because outcomes associated with OHCA remain poor [18].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, uremic conditions can be controlled through advanced technique of RRT even in unstable patients. In spite of the prevalence of technical advances, poor outcomes of AKI-D have been reported worldwide [66,67,80,81]. These data indicate the following possibilities: (1) still insufficient replacement of renal function by current RRT, (2) considerably higher impact of other organ injuries on mortality than AKI, and (3) unrecognized mechanisms such as amplification of distant organ injury by AKI (organ crosstalk).…”
Section: Organ Crosstalkmentioning
confidence: 99%
“…Data obtained from the Japanese Diagnosis Procedure Combination database in 2011 showed that approximately 80% of adult dialysis-requiring AKI (AKI-D) patients in ICUs initially received CRRT [ 65 ]. Unfortunately, the mortality rate of AKI-D patients was unacceptably high (40–50%), although it gradually decreased in the last decades [ 66 , 67 ]. Similar finding of gradual mortality reduction was reported in all the AKI population, whose mortality was approximately 20–30% [ 68 ].…”
Section: Treatmentmentioning
confidence: 99%